The influence of non-steroidal anti-inflammatory drugs with different mechanisms of action on the course of stress reaction, the functional state of kidneys, liver, and heart on the model of acute general cooling - Shtrygol’, Sergiy; Koiro, Olga; Kudina, Olesia; Tovchiga, Olga; Yudkevych, Tetiana; Oklei, Denys (ScienceRise: Pharmaceutical Science, 2022)
Inhibitors of the arachidonic acid cascade have significant potential as the agents for the prevention of severe cold injuries. The results of the previous studies have demonstrated the pronounced frigoprotective properties of certain non-steroidal anti-inflammatory drugs, primarily diclofenac sodium, etoricoxib, darbufelone mesylate, under the conditions of acute general cooling. The aim of the study: to investigate the effect of non-steroidal anti-inflammatory drugs with various mechanisms of action on the course of the stress reaction, the functional state of the kidneys, liver, and heart using the model of acute general cooling. Materials and Methods: The experiment was carried out using 35 outbreed male rats weighing 256±5 g. The studied drugs were administered intragastrically 30 minutes before cold injury modelling: diclofenac sodium at a dose of 7 mg/kg, etoricoxib at a dose of 5 mg/kg, darbufelone mesylate at a dose of 20 mg/kg. Acute general cooling was induced by exposure at –18 °C for 2 hours. The efficacy of the studied drugs was evaluated by the values as follows: the body temperature (measured rectally), the course of a stress reaction according to the criteria of “the stress triad”, the functional state of the kidney and liver according to the changes in the blood serum biochemical parameters, the functional state of the heart according to the electrocardiogram. Results: It was found that etoricoxib and darbufelone mesylate, and especially diclofenac sodium, demonstrate frigoprotective properties, reducing the severity of hypothermia, have stress-protective activity and a beneficial effect on the functional state of the kidneys. All investigated non-steroidal anti-inflammatory drugs prevent a decrease in myocardial contractility (by the effect on the systolic index) and lengthening of the QT interval caused by acute cold injury. Diclofenac sodium, unlike etoricoxib and darbufelone mesylate, does not enhance the effect of acute general cooling on intraventricular conduction. Under acute exposure to cold, no significant changes in the functional state of the liver were observed, including the groups receiving the nonsteroidal anti-inflammatory medicines. Conclusions: The prophylactic administration of the arachidonic acid cascade inhibitors, especially the non-selective COX-2 inhibitor diclofenac sodium, reduces the severity of the stress response, contributes to the maintenance of the renal and cardiac function. There are no significant changes in the functional state of the liver under conditions of the experiment